Cara Meningkatkan Kualitas Pembelajaran Melalui Manajemen Pendidik di SMP Negeri 39 Surabaya - Devi, Navaya Aurelia Kurnia; Putri, Rizka Nadilla; Sari, Dewi Candra Kartika; Windasari, Windasari; Hanivia Cindy, Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
This research is to determine the lack of quality of management learning for educators. Educators still often have schedules that coincide with activities outside of teaching and learning, due to a lack of educational staff. The aim is to find out how to improve the performance of teaching and education staff as well as effective methods for learning activities as a way of assessing and evaluating the performance of teachers between senior and junior, as proven by the existence of a teacher level code. In this research method, the two approaches used to collect data are observation and interviews. Researchers see research subjects directly in the school environment, and interviews involve direct interaction between researchers and research subjects. These two approaches enable researchers to obtain in-depth and accurate information about the research subject. The findings show that teachers often have flexible job desks and the discovery of ways to improve the quality of teacher assessments and evaluations. There is a code for educators who have the right to provide evaluations of teacher performance in the school using the existing system. code to know between senior and junior.